REACTION OF RADIOMETRIC PARAMETERS TO ATMOSPHERIC POLLUTION : PART II -A COMPARATIVE STUDY BETWEEN PAIRS OF STATIONS (MAUSAM, 1994)
In part1,the effect ofatmosphe ric pollution overtime at a ai"-e n location \\'3$ discussed.The parriculate mat ter generated O"U a place is dispersed to surrounding areal> Thus II comp arative stud)'between pain ofstation s is worthwhil e. The effect of indust rial activi ty is clearly seen in the case of New Delhi when compared toJodhpur. However, the changes are not h~ly sienificanl in the case cfihe already de veloped areas like AhmedabadAnd Calcutta. Almost all statio ns show 8 decreasing trend in the net QUlgoina terrestrial radiant ent'rlf)'.